Count Ludwig von Zinzendorf’s Diplomatic Mission to Saint Petersburg in 1755 - Khavanova, Olga (Historical Studies on Central Europe, 2022)
Count Ludwig von Zinzendorf is first and foremost known as an outstanding Austrian economist who greatly contributed to the national reform of finances and administrative efficiency. The early years of his career were spent in the diplomatic service under the guidance and patronage of Count Wenzel Anton von Kaunitz, who placed much hope in the ambitious young aristocrat. One of the significant episodes of Zinzendorf’s diplomatic career was a mission to Russia in 1755. Its formal pretext was to convey the congratulations of the imperial couple to Empress Elizabeth I on the birth of the heir to the throne, Grand Duke Paul. At the same time, Zinzendorf was entrusted with a secret mission of learning more about the main vectors of Russian foreign policy, establishing more confidential relations with the rival groupings at the St. Petersburg court, and promoting closer joint action between Vienna, London, and St. Petersburg against Prussia in the inevitable continental war. The witty analytical mind and exceptional sociability of Zinzendorf allowed him to accomplish both missions brilliantly, the results of which he reported to Kaunitz. This paper considers both the official and unofficial activities of the imperial and Austrian envoy during his visit, the complications he faced, and the solutions he found during his two journeys to Russia in 1755 against the backdrop of Austrian-Russian relations in their heyday on the eve of the Seven Years’ War.